Telemedicine Support Groups for Home Parenteral Nutrition Users. (December 2017) - Nelson, Eve-Lynn; Yadrich, Donna Macan; Thompson, Noreen; Wright, Shawna; Stone, Kathaleen; Adams, Natasia; Werkowitch, Marilyn; Smith, Carol E.
Patients receiving home parenteral nutrition (HPN), a life-sustaining intravenous (IV) infusion that provides nourishment and hydration to patients with short gut or inflammatory bowel diseases, are often isolated and not in visual contact with peers or health providers. One completed clinical trial (Clinical Trials.gov NCT0190028) and 1 ongoing clinical trial (Clinical Trials.gov NCT02987569) are evaluating a mobile videoconferencing-delivered support group intervention for patients on HPN and their caregivers. This home-based telemedicine intervention uses encrypted tablet-based videoconferencing to connect multiple families in real time. The twice-daily IV regimen is challenging for patients who may experience infusion catheter-related bloodstream infections, difficulties with fatigue, loss of sleep, depressive disorders, and worry over the potential life-threatening side effects and the expenses of this therapy. Using secure telemedicine, the facilitated support group intervention aims to enhance HPN home care, daily functioning, and quality of life. The authors provide the rationale for the telemedicine approach with HPN users and caregivers. They provide "how-to" information about the content and process of the facilitated support group sessions via secure videoconferencing. They share lessons learned from the ongoing evaluation of the telemedicine approach.